Optimization of Cannula Visibility during Ultrasound-Guided Subclavian Vein Catheterization, via a Longitudinal Approach, by Implementing Echogenic Technology - Konstantinos Stefanidis; Mariantina Fragou; Nicos Pentilas; Gregorios Kouraklis; Serafim Nanas; Richard H. Savel; Ariel L. Shiloh; Michel Slama; Dimitrios Karakitsos (Critical Care Research and Practice)
Objective. One limitation of ultrasound-guided vascular access is the technical challenge of visualizing the cannula during insertion into the vessel. We hypothesized that the use of an echogenic vascular cannula (EC) would improve visualization when compared with a nonechogenic vascular cannula (NEC) during real-time ultrasound-guided subclavian vein (SCV) cannulation in the ICU. Material and Methods. Eighty mechanically ventilated patients were prospectively enrolled in a randomized study that was conducted in a medical-surgical ICU. Forty patients underwent EC and 40 patients were randomized to NEC. The procedure was ultrasound-guided SCV cannulation via the infraclavicular approach on the longitudinal axis. Results. The EC group exhibited increased cannula visibility as compared to the NEC group (92%±3% versus 85±7%, resp., P<0.01). There was strong agreement between the procedure operators and independent observers (k=0.9, 95% confidence intervals assessed by bootstrap analysis = 0.87 to 0.93; P<0.01). Access time (12.1 s±6.5 versus 18.9 s±10.9) and the perceived technical difficulty of the ultrasound method (4.5±1.5 versus 7.5±1.5) were both decreased in the EC group compared to the NEC group (P<0.05). Conclusions. Echogenic technology significantly improved cannula visibility and decreased access time and technical complexity optimizing thus real-time ultrasound-guided SCV cannulation via a longitudinal approach.